Profile of FKIP UNSRI Students Psychological Flexibility During Pandemic - Alrefi Alrefi; Juntika Nurihsan; Nandang Rusmana; Akbari Akbari (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
This research was motivated by the importance of psychological flexibility in individuals, especially students who were studying during pandemic. This study aimed to get an overview of the psychological flexibility of 2019 batch students at the Faculty of Teaching and Education, Sriwijaya University. Studies on psychological flexibility have been carried out in many countries and researchers have expanded the research to higher education, namely universities. The instrument used was the multidimensional psychological flexibility inventory (MPFI) which consisted of 60 items, but in this study, the researchers only used 30 items. The method used in this research was descriptive quantitative. The results showed that as many as 513 students got an overview of psychological flexibility in the categories in order of high, very high, low, and very low. The results of this study indicated that UNSRI students already had good psychological flexibility, but there were still students who had a level of psychological flexibility in the low and very low categories.